Slow dissent and worldmaking beyond imperial relations in “kamer-amère” (Bitter Cameroon) - Murrey-Ndewa, A (Oxford University Press, 2024)
Working in the subfields of postcolonial geographies of responsibility and Black and African Geographies, my analysis centers on Cameroonian political resistance and practices of worldmaking. From January 2016 to August 2023, political activists experienced a set of difficulties: A wariness and oftentimes hostility to France’s continued support for the authoritarian state, dismissals by state representatives that dissenters were “externally supported,” and misappropriations of the anti-imperial mantel by government representatives. Over the preceding several decades, the state fostered a political environment antagonistic toward Cameroonians of the diaspora, and this was instrumentalized in the widespread dismissal of activists as foreign, foreign-backed, or foreign-influenced. Activists were hesitant but sometimes strategically prepared to call upon transnational groups for attention and political action against repression and violence in Cameroon. In the context of the state’s appropriation of an anti-imperialist ideology, I argue that transnational solidarities must be attuned to and integrated with local politics in Cameroon. Making sense of popular debates regarding (anti)imperialism, (anti)intervention, and transnational solidarity in conditions of authoritarianism matters for political debates across the African continent.